Fine-tuning of type I IFN-signaling in microglia — implications for homeostasis, CNS autoimmunity and interferonopathies. (February 2016) - Goldmann, Tobias; Blank, Thomas; Prinz, Marco
Highlights: Microglia are highly plastic cells controlled by their environment. Low baseline levels of type I IFN are detectable in CNS and sensed by microglia. Microglial type I IFN limits viral spread. IFNβ release mediates microglial phagocytosis of myelin debris in CNS autoimmunity. Dysregulated microglia are involved in the pathogenesis of certain interferonopathies. Abstract : Type I interferons (IFN) are pleiotropic cytokines originally described as molecules used for communication between cells to trigger the protective defenses against viral infections. Upon activation, type I IFN can be produced locally in the central nervous system (CNS) from a number of different cell types including microglia, the CNS-resident macrophages. Increased type I IFN production and signaling in microglia are critically important to limit viral infection and disease progression in multiple sclerosis. However, recent findings suggest that even baseline levels of constitutive IFN expression and secretion are important for homeostasis of the CNS. In fact, in the absence of viral particles chronic elevation of IFN I may be tremendously harmful for the CNS, as assumed for patients suffering from Aicardi-Goutières syndrome, Cree encephalitis or other type I interferonopathies. The highly diverse nature of type I IFN for brain homeostasis during health and disease will be discussed in this report.